Mohsin ki lal gaind - Jafri, Shuja (Say Publishing Karachi, 2002)
"Mohsin ki Lal Gaind" is a charming Urdu story that captures the innocence and imagination of childhood. Centered around a young boy named Mohsin and his beloved red ball, the narrative explores themes of friendship, adventure, and the joys of play. As Mohsin navigates various challenges and experiences, the story illustrates the importance of creativity, resilience, and the bonds formed through shared experiences. Through vibrant storytelling, the book invites readers to reminisce about their own childhood adventures and the simple pleasures that define it.